Migratory process in modern system of the international relations (International relations and international law Journal, 2017)
The article examines the migration process of transformation as a special social phenomenon in the actor of modern international relations and world development. Author tries to reveal the role of migration in the process of formation of the foreign policy of modern states, its impact on the global demographic situation, the global economy, changes in the international security concepts. Taking into account influence on development of regional collaboration and common regional steady development, some theoretical aspects of migratory processes were investigated. Functions of competent structures are taken into account providing economic and social development in a sphere management of migratory processes in international relations.
Keywords: migration process; globalization; labor migration; world developments; international relations; demography; world politics; security